AB0046 Endocannabinoid System and Systemic Lupus Erythematosus - Navarini, L.; Mozetic, P.; Margiotta, D.P.E.; Basta, F.; Saracini, S.; Afeltra, A.; Maccarrone, M.; Bisogno, T. (Annals of the rheumatic diseases, 2016)
BackgroundEndocannabinoid (eCB) system comprises endogenous lipid mediators (eCBs) like N-arachidonoylethanolamine (anandamide, AEA) and 2-arachidonoylglycerol (2-AG), along with their specific G protein-coupled type-1 (CB1) and type-2 (CB2) cannabinoid receptors, and the proteins responsible for eCB biosynthesis, inactivation, transport, and accumulation. In recent years, many studies have evaluated the role of eCBs in the homeostasis of the immune system. Notably, AEA and the eCB-like molecule N-palmitoylethanolamine (PEA) seem to be anti-inflammatory mediators, while 2-AG is implicated in both pro-inflammatory and anti-inflammatory functions. Moreover, the effects of eCBs on immune system seem to be mostly mediated by CB2, more expressed in immune cells than by CB1. The latter receptor, instead, is more implicated in neurotransmission. Several studies have already investigated the role of eCB system in different immune-mediated diseases, such as multiple sclerosis and type-1 diabetes.ObjectivesTo investigate the role of eCB system in patients with systemic lupus erythematosus (SLE) and age and sex matched healthy subjects.Methods10 female patients with SLE and 10 healthy subjects were enrolled from outpatient clinic of Campus Bio-Medico University of Rome. Every SLE patient was positive for anti-dsDNA antibodies and/or exhibited hypocomplementemia with or without hypergammaglobulinemia, ENA or aPL positivity. None of them was treated with biological therapy at the time of enrolment, nor with steroid bolus in the previous six months, while treatment with conventional immunosuppressants was allowed. SELENA-SLEDAI and BILAG were used to assess disease activity and SDI as damage index. AEA, 2-AG and PEA levels were quantified in plasma of SLE patients and healthy controls by using liquid chromatography-tandem mass spectrometry (LC-MS).ResultsNo significant difference among ages was found in the two groups (SLE patients 37.9±5.9 years, healthy subjects 37.8±6.2, p=ns). In SLE patients, 80% of the subjects exhibited low C3, 50% low C4, 90% anti-dsDNA positivity; 30% of them were not taking glucocorticoids, 20% ≤5 mg of daily prednisone and 50% >5 mg of daily prednisone; 70% were taking conventional immunosuppressive treatment and 80% were taking hydroxychloroquine. Value of the disease activity score evaluated by SELENA-SLEDAI was assessed as 6±4.7; 10% of the patients exhibited at least 1 BILAG A and 60% at least 1 BILAG B; value of the damage index evaluated by SDI was assessed as 0.6±0.8. eCBs was significantly altered in SLE patients. In particular, plasma levels of 2-AG were significantly increased in SLE patients compared to healthy controls (p=0.005), while no differences were found in AEA and PEA concentrations between the two groups.ConclusionsOur results demonstrate, for the first time, an alteration of eCB system in SLE patients; these data may help to better understand the role of lipid mediators in SLE pathogenesis.ReferencesFezza F. et al. Molecules. 2014; 19:17078–106.Gruden G. et al. Br J Pharmacol. 2015. doi: 10.1111/bph.13226Disclosure of InterestNone declared